9-3m+mn-3n=

Simple and best practice solution for 9-3m+mn-3n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-3m+mn-3n= equation:


Simplifying
9 + -3m + mn + -3n = 0

Solving
9 + -3m + mn + -3n = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -3m + mn + -9 + -3n = 0 + -9

Reorder the terms:
9 + -9 + -3m + mn + -3n = 0 + -9

Combine like terms: 9 + -9 = 0
0 + -3m + mn + -3n = 0 + -9
-3m + mn + -3n = 0 + -9

Combine like terms: 0 + -9 = -9
-3m + mn + -3n = -9

Add '3n' to each side of the equation.
-3m + mn + -3n + 3n = -9 + 3n

Combine like terms: -3n + 3n = 0
-3m + mn + 0 = -9 + 3n
-3m + mn = -9 + 3n

Reorder the terms:
9 + -3m + mn + -3n = -9 + 3n + 9 + -3n

Reorder the terms:
9 + -3m + mn + -3n = -9 + 9 + 3n + -3n

Combine like terms: -9 + 9 = 0
9 + -3m + mn + -3n = 0 + 3n + -3n
9 + -3m + mn + -3n = 3n + -3n

Combine like terms: 3n + -3n = 0
9 + -3m + mn + -3n = 0

The solution to this equation could not be determined.

See similar equations:

| 62.9296(100-y)+64.9278=63.546 | | -8x-9=23 | | 8t=7t+2/3 | | -11-4t=6+3(11-3t) | | 2x^2-5+167=0 | | -(1+7v)-7b=111 | | 14x+22=7x-1 | | x(x-4)=x+5x+8 | | 10h-7=9h-26 | | X=96+7x | | 42=6-2/3x | | 7/10d-21/10 | | 4x-70=12y+2 | | 4p^2-2-p=2-p | | 5x-7x=7 | | -3-12-5+2/3= | | m^4/2m^4 | | 2x/3-5=x-1 | | b/5+1/6=13 | | .25x-2.5=1x+1 | | 6k-1k=5k+10 | | 133=-3(7n+4)-2 | | 10d+9=-7+2(4d+3) | | 5x-2x+4=10 | | 1000(9x-10)=50(656+100x) | | 2(x-7)+x=3(x-6)+4 | | y-60=7x-35 | | (w-6)=3(w+1) | | -12/-4+12/6+3= | | 4x-5x=-4 | | 4x^2+2=402 | | 4y-(-10)=26 |

Equations solver categories